The lived experience of patients with obesity at a metropolitan public health setting - Fiona M. Pazsa; Catherine M. Said; Kimberley J. Haines; Eloise Silburn; Melina Shackell; Danielle Hitch (BMC, 2022)
Abstract Background Patient-centred care models for acutely hospitalised people living with obesity are poorly understood and the quality of evidence low. Objective The aim of this study was to explore and better understand the lived experience of people living with obesity, in the inpatient hospital context. Design A qualitative methodology using Interpretative Phenomenological Analysis (IPA) was used. Data were collected via a single semi-structured interview with each participant. Setting and participants The study was completed at a metropolitan public health service. Ten previously hospitalised patients who live with obesity were included. Results Three main themes emerged: meeting physical care needs of people with obesity on hospital wards, interpersonal interactions between patients and healthcare professionals, and the psychosocial impact of being obese in the hospital setting. Priorities included timely provision of appropriate equipment and infrastructure design to meet care needs and facilitate better wellbeing. To improve patient experience, an emphasis on basic principles of quality care provision to enhance interpersonal interactions, along with improved awareness of the impact of weight bias and obesity stigma in healthcare are supported. Participants found hospitalisation stressful, but valued support from healthcare professionals regarding weight loss. Discussion These data provide new insights in to the lived experience of people living with obesity in the hospital setting. Items which are low cost, such as appropriately sized chairs and gowns, as well facilitators to independent mobility such as electric wheelchairs are suggested to improve both experience and care outcomes. Interpersonal interactions demonstrated obesity stigma in the hospital setting, with participants expressing the desire for more appropriate communication. People living with obesity self-reflected in the inpatient setting, suggesting that staff should be trained to utilise the opportunity to provide weight loss advice. Conclusions The themes identified in this study provide insight into the lived experience of people with obesity in hospital. This understanding provides direction for the development of improved models of care for people living with obesity in this setting and beyond.